Effect of deposition pressure on the microstructure and thermoelectric properties of epitaxial ScN(001) thin films sputtered onto MgO(001) substrates. Issue 5 (16th February 2015) - Burmistrova, Polina V.; Zakharov, Dmitri N.; Favaloro, Tela; Mohammed, Amr; Stach, Eric A.; Shakouri, Ali; Sands, Timothy D.
Abstract: Abstract : Four epitaxial ScN(001) thin films were successfully deposited on MgO(001) substrates by dc reactive magnetron sputtering at 2, 5, 10, and 20 mTorr in an Ar/N2 ambient atmosphere at 650 °C. The microstructure of the resultant films was analyzed by x-ray diffraction, scanning electron microscopy, and transmission electron microscopy. Electrical resistivity, electron mobility and concentration were measured using the room temperature Hall technique, and temperature dependent in-plain measurements of the thermoelectric properties of the ScN thin films were performed. The surface morphology and film crystallinity significantly degrade with increasing deposition pressure. The ScN thin film deposited at 20 mTorr exhibits the presence of <221> oriented secondary grains resulting in decreased electric properties and a low thermoelectric power factor of 0.5 W/mK 2 at 800 K. The ScN thin films grown at 5 and 10 mTorr are single crystalline, yielding the power factor of approximately 2.5 W/mK 2 at 800 K. The deposition performed at 2 mTorr produces the highest quality ScN thin film with the electron mobility of 98 cm 2 V −1 s −1 and the power factor of 3.3 W/mK 2 at 800 K.